ROI Basics, 2nd Edition - Phillips, Jack; Phillips, Patricia (Association for Talent Development, 2019)
Your essential guide to calculating return on investment. Build and refine your measurement and evaluation skills through ROI Basics, perfect for beginners challenged to implement a comprehensive evaluation process as well as those taking a proactive approach to accountability. Its five-level evaluation framework includes: Level 1: Reaction and Planned Action Level 2: Learning Level 3: Application and Implementation Level 4: Impact Level 5: Return on Investment ROI Basics provides a baseline exploration of ROI for the talent development function and the steps to successful evaluation: evaluation planning, data collection, data analysis, and results optimization. In this second edition, experts Patti and Jack Phillips go deeper into aligning programs to the business, detecting payoff needs, and identifying specific business measures that need to improve. They explore how the process applies beyond training to talent development and suggest how new technologies can influence ROI adoption and implementation in your organization. This updated book offers a review of two essential-and often overlooked-steps in the ROI process: isolating program impact and sustaining momentum.